PENERBITAN SERTIFIKAT HAK MILIK PENGGANTI KARENA HILANG OLEH AHLI WARIS YANG DISEBABKAN OLEH BENCANA ALAM - Fatmala, Faiqa (Universitas Tadulako, 2020)
Land registration is essentially aimed at ensuring the right of the landowner. The publication of a certificate is a safeguard to the landowner of his rights to the land. Ownership of the land is hereditary, but if the certificate of ownership is lost, what evidence is used by the heirs in the process of issuing the replacement certificate, and what remedies it can do. In this paper using the type of legal research that is normative by finding the truth of coherence. Proof of ownership by the heirs is a certificate of inheritance endorsed by the sub-district or village head, in the process of issuing the replacement certificate lost due to natural disaster done first checking the physical data and juridical data and then held the announcement. If after 30 (thirty) days after the announcement of the issuance of a replacement certificate and no party has stated the objection then the Land Office will issue a replacement certificate that has been lost due to natural disaster